PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA PADA MODEL ‘CORE’ (CONNECTING, ORGANIZING, REFLECTING, EXTENDING) DENGAN PENDEKATAN KONTEKSTUAL POKOK BAHASAN PELUANG UNTUK SISWA SMA KELAS XI - Nur H, Fiqih; Hobri, H; Suharto, S (Department of Mathematics Education , University of Jember, 2014)
Abstract: This research aims to know how the process and the result of developing mathematics learning materials onCORE model (Connecting, Organizing, Reflecting, Extending) with contextual Approach of opportunities topic at grade XI senior high school. This study developes lesson plan,worksheet, evaluation test, and Studentbooks. The development mathematics learning materials standardized CORE model with contextual approach. This development model refers to 4-D Thiagarajan and Sammel & Samel models. This four steps are defining step, designing step, developing step, and disseminating step. The product of learning materials development standardized by CORE model with contextual approachforopportunitiestopic has fulfilled the validation criteria, practicability, and effectiveness. Key Words: Learning Materials, CORE Model, CTL, Opportunities.4-D Model